EVALUATION OF SOME CHEMICALS FOR THE CONTROL OF BLUE STAIN FUNGUS AND PINHOLE BORER ON FRESHLY SAWN COCONUT TIMBER - R. N. Palomar (International Coconut Community Journal, 1989)
An investigation was made to determine the relative performance of some chemicals against growth of blue stain fungus and attack of pinhole borer on freshly‑sawn coconut timber during the drying process. The fungicides used were Farmay Plus, Azaconazole and the standard chemical combination of Sodium Pentachlorophenate, BHC and Borax Pentahydrate. Cislin, an insecticide, was mixed with either Farmay Plus or Azaconazole solution. Results after 12 weeks of air drying showed that all fungicides failed to give the desired protection against blue staining. Performance ratings of planed wood samples were within the range of heavy to severe stain infection. Although none of the fungicides was able to effectively control the blue stain fungus, their respective performance have been to some extent ascertained. On the other hand, Cislin showed an acceptable level of protection from pinhole borer infestation on coconut lumber.